Carbon Pricing as a Climate Policy Instrument: Global Lessons, Challenges, and Future Directions - Rismanto, Hilman; Lestari , Putri Ayu (Indonesian Scientific Publication, 2025)
Carbon pricing has become a central instrument in global strategies to mitigate climate change, yet its economic, social, and environmental implications remain contested. This study provides a narrative review synthesizing literature from Scopus, Web of Science, and Google Scholar to evaluate the effectiveness of carbon pricing mechanisms. Keywords including carbon tax, emissions trading systems, carbon pricing mechanisms, and economic implications guided the selection of peer-reviewed studies published between 2000 and 2025. Inclusion criteria focused on research addressing economic growth, innovation, social equity, and environmental outcomes across developed and developing contexts. Results show that carbon pricing fosters green innovation, reduces emissions in energy and transport, and generates fiscal revenues that can finance social and environmental programs. However, outcomes vary significantly: industries with high resource dependence face cost burdens, low-income households are disproportionately affected, and developing countries struggle with institutional weaknesses and carbon leakage. Comparative analysis demonstrates that both carbon taxes and cap-and-trade systems can be effective when complemented by redistributive mechanisms, strong institutions, and integration with broader policy frameworks. The discussion highlights systemic political, economic, and institutional factors that influence success and identifies gaps in longitudinal and social impact research. Findings suggest that well-designed carbon pricing can balance mitigation and equity objectives, but future research must expand comparative analyses and explore hybrid policy models. The study underscores carbon pricing as an indispensable yet context-sensitive tool for achieving sustainable low-carbon transitions.